Ligações em estruturas de aço utilizando emendas com parafusos de alta resistência solicitadas na flexão simples - Pereira, Ronivon Soares (2014)
Structure is designed to have satisfactory performance given the quality standards and requirements in the construction of which designers need. Increasingly, large metal structures are developing in this competitive market, where performance and quality of the project depend on manufacturing processes of materials, assembly, inspection and maintenance. The metal structures, especially those of type I profiles of parallel laminated tabs depend on the quality control in your bolted splices. This study aimed to analyze the bearing capacity of steel beams supported by profiles consist of type I rolled parallel flanges with two axes of symmetry, being endowed with seams with high strength bolts type ASTM A325, diameter 19 mm. Eight beams with a length of 3000 mm, two reference beams were tested. In the remaining six beams splices were made at different positions varying the amount of seams. All models have been efforts required by simple bending to failure, by analyzing the vertical displacement, torsional displacement relative and specific deformations of steel. The connections of the beams withstood the test flexural not being observed and no break on the bolts or the connecting plate, featuring breaking loads between 74% and 85% for beams of series with connections. Considerably beams with connections showed no breaking loads far below the reference beams with breaking loads between 78% and 100%. The results indicate that the beams with bolted with high strength bolts connections are sturdy and therefore can be used by designers in the field of steel structure as another option.